2015
DOI: 10.1111/jfcj.12028
|View full text |Cite
|
Sign up to set email alerts
|

Family Drug Court, Targeted Parent Training and Family Reunification: Did this Enhanced Service Strategy Make A Difference?

Abstract: This article reports findings from an evaluation of reunification outcomes for children and families who participated in a family drug court (FDC) that incorporated the use of two innovative evidence-based parenting programs. In addition to comprehensive FDC services, families participated in the Strengthening Families Program and Celebrating Families! TM programs in a sequential format. Data analyses were conducted on a sample of 214 children whose child welfare cases were adjudicated through the FDC and 418 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Child welfare opinion leaders have identified evidence‐based behavioural parenting interventions (EBPIs) as a critical strategy for addressing maltreatment and improving child welfare outcomes (Barth et al, ; Horwitz, Chamberlain, Landsverk, & Mullican, ), including for families affected by substance use (Barth, ). Brook and colleagues have also shown that a group‐based EBPI promotes reunification among parents affected by substances with children in foster care (Brook, Akin, Lloyd, Johnson‐Motoyama, & Yan, ; Brook, Akin, Lloyd, & Yan, ; Brook, McDonald, & Yan, ). Despite efforts to expand EBPIs to child welfare, a formidable barrier is parental engagement and service completion as an intervention has little chance of improving outcomes unless families engage in the intervention (Berliner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Child welfare opinion leaders have identified evidence‐based behavioural parenting interventions (EBPIs) as a critical strategy for addressing maltreatment and improving child welfare outcomes (Barth et al, ; Horwitz, Chamberlain, Landsverk, & Mullican, ), including for families affected by substance use (Barth, ). Brook and colleagues have also shown that a group‐based EBPI promotes reunification among parents affected by substances with children in foster care (Brook, Akin, Lloyd, Johnson‐Motoyama, & Yan, ; Brook, Akin, Lloyd, & Yan, ; Brook, McDonald, & Yan, ). Despite efforts to expand EBPIs to child welfare, a formidable barrier is parental engagement and service completion as an intervention has little chance of improving outcomes unless families engage in the intervention (Berliner et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Family drug courts (FDCs) are specialized courts within the justice system, which handle cases of child abuse and neglect that involve substance use by the child's parents or guardians (Brook et al 2015;Chuang et al 2012). FDCs are one method of addressing parental substance use disorders and parenting issues within the court and child welfare systems, using a collaborative, family-centered approach (Children and Family Futures 2015).…”
Section: Family Drug Courtsmentioning
confidence: 99%
“…FDCs are one method of addressing parental substance use disorders and parenting issues within the court and child welfare systems, using a collaborative, family-centered approach (Children and Family Futures 2015). Also called family treatment courts, family treatment drug courts, or family dependency treatment courts, FDCs operate as alternatives to traditional family courts or dependency courts and work to balance the rights and needs of both parents and children (Brook et al 2015). The overall goal of FDCs is to reduce child maltreatment by treating parents' underlying substance use disorders through a coordinated and collaborative approach that involves a multitude of agencies and professionals such as the court system, child protective services (CPS) or child welfare, substance use treatment providers, and the attorneys involved in the case (Pach 2008;Gifford et al 2014).…”
Section: Family Drug Courtsmentioning
confidence: 99%
See 2 more Smart Citations